2021
DOI: 10.1038/s41598-021-99815-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro impact preliminary assessment of airborne particulate from metalworking and woodworking industries

Abstract: Inhalation is the main route of exposure to airborne pollutants. To evaluate the safety and assess the risks of occupational hazards different testing approaches are used. 3D airway epithelial tissues allow to mimic exposure conditions in vitro, generates human-relevant toxicology data, allows to elucidate the mode of action of pollutants. Gillian3500 pumps were used to collect the airborne particulate from woodworking and metalworking environments. EpiAirway tissues were used to model half working day (4 h), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition, Pavlovska et al investigated the biological effects of airborne particulates collected in woodworking and metalworking industries both on EpiAirway 3D human small airway epithelial cells exposed for 4 h (half a working day), 8 h (full working day) and 72 h (three working days) and on A549 lung epithelial cells that were continuously exposed for 96 h. The obtained data showed that exposure to these polluting particles exerted minor acute effects on the morphology and viability of both A549 cells and EpiAirway tissues. However, a marked reduction in EpiAirway tissue viability after 8 h of exposure to woodworking particles and a slight reduction in tissue viability after 72 h of exposure to metalworking particles were observed [24].…”
Section: Introductionmentioning
confidence: 92%
“…In addition, Pavlovska et al investigated the biological effects of airborne particulates collected in woodworking and metalworking industries both on EpiAirway 3D human small airway epithelial cells exposed for 4 h (half a working day), 8 h (full working day) and 72 h (three working days) and on A549 lung epithelial cells that were continuously exposed for 96 h. The obtained data showed that exposure to these polluting particles exerted minor acute effects on the morphology and viability of both A549 cells and EpiAirway tissues. However, a marked reduction in EpiAirway tissue viability after 8 h of exposure to woodworking particles and a slight reduction in tissue viability after 72 h of exposure to metalworking particles were observed [24].…”
Section: Introductionmentioning
confidence: 92%
“…21 Nevertheless, comparison of effects induced by SiO 2 NPs with three sizes (50, 200, and 400 nm) showed that the larger-sized silica NP induced higher activity of alkaline phosphatase, suggesting their higher stimulatory effects on osteogenic differentiation of human mesenchymal stem cells. 22 Given the diversity of SiO 2 NP size (50 to 500 nm) in a practical scenario, 23,24 it would be of high importance to investigate their particle size-related effects on megakaryocytic maturation and differentiation by testing NPs with the size range of environmental relevance.…”
Section: Introductionmentioning
confidence: 99%